Combinatorial optimization : 5th International Symposium, ISCO 2018, Marrakesh, Morocco, April 11-13, 2018, Revised selected papers /: 5th International Symposium, ISCO 2018, Marrakesh, Morocco, April 11-13, 2018, Revised selected papers. (2018) - Unknown
No abstract available